PERANCANGAN PROMOSI WISATA DAN BUDAYA KOTA PADANG BUKU MEWARNAI MY CITY MY WORLD SEBAGAI MEDIA - OCVA ARSIDA, Hendra Afriwan, S.Sn., M.Sn., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
Coloring book My City My World is a coloring book at the same time discussing the sale of books and cultural tourism in the city of Padang. Coloring book with targets teenagers audiencenya aims to promote tourism and culture in the city of Padang. Besides can color, we can also find out about travel and culture in the city of Padang. The design of this illustration is expected to contribute to and benefit all groups with a coloring book that he designed an appealing and can provide the necessary information while visiting the city of Padang.The design method used by the authors is the observation and documentation. Then proceed with the data analysis method using the analysis of the 5W + 1H (what, where, when, who, why and how) and a creative approach.Illustrations in the book coloring My City My World using decorative illustration without leaving its original shape, so it will attract more audience in coloring. In addition, the illustration has been designed also to add headline which serves to explain the illustration so that the audience will understand what is being colored image.Keywords: Illustration, Coloring Book, Padang.